Antimicrobials 2013
DOI: 10.1007/978-3-642-39968-8_7
|View full text |Cite
|
Sign up to set email alerts
|

Lantibiotics and Similar Peptides Produced by and Active on Gram-Positives: Discovery, Development and Perspectives

Abstract: Lantibiotics are a group of ribosomally synthesised peptides that contain post-translational modifications consisting of (methyl)lanthionine residues forming bridges that confer them characteristic structures. Most lantibiotics are antibacterials that bind to the cell wall precursor lipid II. They can be rod shaped or globular depending on the distribution of the lanthionine residues. Their biosynthetic pathway is relatively simple when compared to other secondary metabolites. Due to this simplicity, genetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…In 2007, a report on a phase II clinical studies on aerosolized duramycin (Moli1901) for the treatment of cystic fibrosis revealed exciting results [ 131 ]. This drug, which is jointly developed by Lantibio (North Carolina, USA) and AOP Orphan Pharmaceuticals (Vienna, Austria) [ 132 ] has completed phase II clinical trials for the treatment of cystic fibrosis [ 133 ].…”
Section: Pharmaceutical Prospectsmentioning
confidence: 99%
“…In 2007, a report on a phase II clinical studies on aerosolized duramycin (Moli1901) for the treatment of cystic fibrosis revealed exciting results [ 131 ]. This drug, which is jointly developed by Lantibio (North Carolina, USA) and AOP Orphan Pharmaceuticals (Vienna, Austria) [ 132 ] has completed phase II clinical trials for the treatment of cystic fibrosis [ 133 ].…”
Section: Pharmaceutical Prospectsmentioning
confidence: 99%